2009
DOI: 10.7202/037781ar
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic diversity and toxicological assessment of Cyanobacteria in Moroccan inland waters

Abstract: AbstractResearch on the ecology, biodiversity and toxicology of cyanobacteria in Moroccan inland waters has been carried out since 1994. The results demonstrate the existence of several taxa of cyanobacteria. Most of them are toxic, bloom‑forming species present in various water bodies of the country. The present study follows upon this earlier work and spans the 2003-2006 period. The major aim was to update and supplement the existing national cyanobacteria inventory and to is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…cf. biceps is found mainly attached to substrate (Komárek and Anagnostidis, 2005;Douma et al, 2009;Klemenčič et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cf. biceps is found mainly attached to substrate (Komárek and Anagnostidis, 2005;Douma et al, 2009;Klemenčič et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…cf. biceps is a species that lives primarily attached to substrate (Komárek and Anagnostidis, 2005;Douma et al, 2009;Klemenčič et al, 2010) and therefore belonging to MP codon. In the Castanhão reservoir, the most remarkable environmental change associated to the emergence of Pseudanabaena sp.1 in phase II (absent in phase I) was the increase in Secchi depth and the decrease in ammonium-N.…”
Section: Discussionmentioning
confidence: 99%
“…None of them could also be classified as a new variant of the known peptides group commonly occurring in cyanobacterial taxa. So far, the only peptides identified in Pseudanabaena species were microcystins [ 13 , 14 , 15 , 16 , 17 , 18 ]. Based on the analyses of MS/MS spectra it can be concluded that peptides detected in P. galeata CCNP1313 are composed of proteinogenic amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…As cellular extracts were used in these studies, the active agents could not be identified. Some Pseudanabaena chemotypes produce known toxins, such as microcystins [ 13 , 14 , 15 , 16 , 17 , 18 ], anatoxin-a [ 18 ], and saxitoxin [ 18 ]; therefore, these compounds could be responsible for the observed effects. Pseudanabaena has also been explored as a source of metabolites with biotechnological and pharmaceutical potential [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benthic cyanobacteria that produce microcystins (MCs) were first detected and characterised in communities in alpine lakes [ 1 ]. Since then, their presence in benthic communities in Spain [ 2 , 3 ], California [ 4 ], Egypt [ 5 ], Morocco [ 6 , 7 ], New Zealand [ 8 ], and other countries [ 9 ] has been reported. More recently, the presence of benthic cyanobacteria has been demonstrated in 30% of fordable rivers in California, and the number of potentially toxic genera has increased [ 10 ].…”
Section: Introductionmentioning
confidence: 99%